Analisis Ruang Percepatan: Dinamika Pendidikan Di Era Pandemi Covid 19 - Hanafi Saputra; Yeni Marcelawati (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
This article aims to elaborate on the dynamics of the implementation of Indonesian education using the perspective of Paul Virilio's space for acceleration as a form of the phase of acceleration space during the Covid-19 crisis. Starting from the fact that education as the standard determining the country's progress has experienced segregation during the Covid-19 pandemic. Activities related to the transfer of knowledge, which can usually be carried out in a physical space with clear boundaries of space and distance, such as in educational institutions, suddenly shift to a space that is no longer limited by space and distance. These conditions then produce various dynamics that have an impact on the implementation of education. Because the use of space for acceleration in the world of education will have a significant impact on science. This is increasingly interesting, especially in connection with the condition of Indonesia, which still has various unresolved homework in the world of education. The data in this article were obtained from books, news, research reports, journals, and internet sources. By using a qualitative exploratory method through a literature approach to answering the question of how the dynamics of the implementation of Indonesian education in the midst of the Covid-19 pandemic in Paul Virilio's space for acceleration, it is known that online learning is a place to capitalize on the commodification of education through media platforms as an arena for implementing education. Besides, inequality in the distribution of capital such as facilities and access to learning creates increasingly visible gaps in society. Then the use of space for acceleration leads to a crisis of intelligence and a crisis of civilization in a country due to the inadequate implementation of education during the Covid 19 period.